Faktor Penyebab Menurunnya Motivasi Anak dalam Belajar Membaca Al-Qur’an (Studi Kasus di TPQ An-Nuriyah Kelurahan Majapahit Kecamatan Batauga) - Riskawati Galampa; La Jusu; Basri Basri (Journal of Innovative and Creativity, 2025)
The purpose of this study is to ascertain the reasons behind the decrease in the motivation of children (13–16 years old) to learn to read the Quran and the measures taken to boost that motivation at TPQ An-Nuriyah, Majapahit Village, Batauga District. This research uses a case study research design and a qualitative, descriptive methodology. Techniques for gathering data included recordkeeping, interviews, and observation. According to the research results from TPQ An-Nuriyah in Majapahit Village, Batauga District, internal factors namely, a lack of children's motivation due to boredom, laziness, and a lack of religious understanding are the main causes of the decline in children's motivation to learn to read the Quran. A lack of parental supervision, instructional strategies, social interaction, and the impact of technology, such as gadget addiction, are examples of external variables. In addition, Quranic teachers use guidance, incentives, and resources to help kids become more motivated to learn to read the Quran. Parents of the kids are working to increase their children's motivation to learn the Quran by teaching them to memorize the Quran at home, offering guidance, and reminding them of recitation time.